Tandem reactions combining Diels-Alder reactions with sigmatropic rearrangements - Franz, Andreas; Neier, Reinhard; Schoepfer, Joseph (My University, 1996)
The developpement of tandem reactions combining Diels-Alder reactions with sigmatropic rearrangements and their application in synthesis will be discussed. [Equation Omitted]. [on SciFinder(R)]